Thermodynamic and economic study of PEMFC stack considering degradation characteristic. (1st May 2021) - Chen, Xi; Xu, Jianghai; Yang, Chen; Fang, Ye; Li, Wenbin; Zhang, Yan; Wan, Zhongmin; Wang, Xiaodong
Highlights: A degradation model is proposed to predict the life and degradation process of PEMFCs. The transient voltage, degradation rate and electric power at different operating currents over the lifetime are discussed. The effects of fuel consumption, fuel price and degradation rate on the total cost of stack are studied. Abstract: Degradation phenomena is the key factor restricting the performances of Proton Exchange Membrane Fuel Cell (PEMFC) in its whole life period. This paper presents a degradation model for predicting the lifetime and degradation progress of PEMFC stack. The thermodynamic and economic performances of PEMFC stack over the lifetime are conducted. In thermodynamics, the transient voltage, degradation rate, electrical power and efficiency at various working current are discussed. In economics, the fuel consumption, effects of fuel price and degradation rate on total cost of PEMFC stack during the whole lifetime are studied. The results show that high working current accelerates the cell degradation, largely shorten the lifetime of PEMFC stack. With the raise of current, the degradation rate of singe cell climbs to 4.87 × 10 - 5 V h −1, lifetime shorten by 25.9%. The electrical efficiency of PEMFC stack at 80A can reach 38.3%. Furthermore, with the raise of degradation rate, the fuel consumption and total cost increases, the average cost of PEMFC stack fluctuates from 17.6 to 34.5 $ h −1 .